Towards financial inclusion in East java : assessment of the issues from the perspective of Islamic microfinance of the clients and experts - Maulana, Hartomi (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
Even though the Indonesian financial industry is growing exponentially, a significant population under poverty remains financially excluded from the mainstream financial facilities. Even when financial services are available, certain low-income group may exclude using conventional micro-financing on religious grounds. This indicates that religious values appear to be an important issue to shape the attitudes of the rural clients who are predominantly Muslim. This study was based on the concern for appraising the appropriateness of Islamic microfinance to enhance financial inclusion in Indonesia. The first objective is to examine the main factors that hinder micro-entrepreneurs from accessing financing from mainstream financial services in Indonesia's province of East Java. The second is to examine factors that affect Muslim clients' behaviour in participating in Islamic microfinance, in this case BMT (Baitul Maal wat Tamwil). The third is to investigate Islamic microfinance practitioners and Shari'ah scholars' views on the issues and challenges of promoting BMT in Indonesia. The variables used in the study consists of a theoretical framework comprising five barriers to accessing finance, namely affordability barrier, eligibility barrier, accessibility barrier, availability barrier and religious barrier. Decomposed Theory of Planned Behaviour is also used as a research framework for accessing clients' participation in Islamic microfinance. Relevant information was collected from BMT clients in East Java using a survey questionnaire and interviews with Islamic microfinance experts. The Structural Equation Modelling (SEM) was used as main analytical tool. The study revealed that the five variables are indeed factors that contribute to the financial exclusion of micro-entrepreneurs in mainstream financial services. In terms of clients participating in BMT, among three main beliefs, only perceived behavioural control (PBC) was found to have a positive and significant impact on clients' participation in BMT. With regard to antecedents' influence on their beliefs, relative advantage, awareness, normative beliefs and self-efficacy were significant. The qualitative findings are consistent with the main issues and challenges of promoting BMT identified in the literature, particularly human capital, regulation, role of the government and lack of capital issues.